ANALISIS PERBEDAAN LITERASI KEUANGAN NASABAH CREDIT UNION DAN NASABAH BAITUL MAAL WATTAMWIL (SURVEI PADA CREDIT UNION MINO MARTANI SOKARAJA DAN BAITUL MAAL WATTAMWIL MUHAMMADIYAH DANA MENTARI PURWOKERTO) - Utami, Hastin Tri (BISNIS, 2018)
This paper aims to analyze the difference between financial literacy of Credit Union Customers who have financial education and Baitul Maal Wattamwil Customers who do not have financial education in term of behavior, knowledge and attitude. The data was collected by conducting survey. The object of this study is 60 persons consist of 30 credit union customers and 30 BMT customers. The result of this study shows that there is no significance difference between financial literacy of Credit Union Customers who have financial education and Baitul Maal Wattamwil Customers who do not have financial education in term of behavior, knowledge and attitude. This study is only to examine the difference between the financial literacy of the CU customer who has get financial education and BMT customer who has not gotten financial education. The next study is hoped to analyze the different object before and after given financial education or different objects such as students, banking customers, and housewife. This study is only analyzing in term of three aspects; behavior, knowledge and attitude of the customers. Therefore, the further study can enhance other aspects such as gender, education level, etc.